SENYAWA ANTIMAKAN PADA MINYAK BIJI NYAMPLUNG (Calophyllum inophyllum L) - Sri Rahayu Santi (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
Isolation of antifeedant active compound from sarcocarp of Calophyllum inophyllum L. with Epilachna sparsa larvae were use as bioindicator was conducted. The antifeedant assay was performed on crude extract, fraction, and isolate. Dried sarsocarp powder of nyamplung was extraction with 6L metanol to yield 186,38 g dark brown extract. This Active extract was then fractionated into n-hexane to yield 19,27 g yellow oil.. Separation of 2 g oil was done using silica gel column chromatography with chloroform n-hexane (2:1) as eluent and five group of fraction were obtained with F5 the most active isolat wich showed 27,89% antifeedant activity at 200 ppm was found and relatively pure . Base on analysis of Gas chromatography-mass spectroscopy and data base NISTO2.L the antifeedant active isolat were identify as methyl-14-methyl-pentadecanoid acid, n-hexanedecanoid acid, methyl-9,12-octadecadienoic, methyl-9-octadecenoic acid, methyl-octadecanoic, 9-octadecenoic acid, octadecanoic acid, and the last peak has a moleculer ion at 341.